Base-controlled product switch in the ruthenium-catalyzed protodecarbonylation of phthalimides: a mechanistic study. Issue 1 (6th December 2019) - D'Alterio, Massimo Christian; Yuan, Yu-Chao; Bruneau, Christian; Talarico, Giovanni; Gramage-Doria, Rafael; Poater, Albert
Abstract : Mechanism of the ruthenium-catalyzed protodecarbonylation of phthalimides into benzamides elucidated by experiments and calculations: the various roles of the bases responsible for the control of chemoselectivity. Abstract : The whole reaction mechanism of the ruthenium-catalyzed protodecarbonylation of N -substituted phthalimides into secondary amides was unravelled by a combined experimental and theoretical study. The chemoselectivity of the reaction, which is catalyzed by para -cymene coordinated Ru(ii ) species all over the catalytic cycle, is exclusively controlled by the unique roles of the bases. Meanwhile, in the presence of K2 CO3 or KOH at high temperatures, the same product (benzamide) is mainly formed, whereas at low temperatures, KOH led to an unexpected side-product (phthalamic acid) and no reactivity was observed with K2 CO3 . The non-covalent interactions between the potassium cations and the different carbonyl groups in the molecules are key to providing a thermodynamically favourable pathway with energetically accessible transition states. The unexpected formation of carbon dioxide (CO2 ) in the course of the reaction originates from the phthalimide substrate and the base K2 CO3 in two different elementary steps, respectively.